The impact of retailer's corporate social responsibility activities on customer loyalty at Negeri Sembilan, Malaysia / Shaikh Multazim Hasan Ali ... [et al.] - Hasan Ali, Shaikh Multazim; Munusami, Chandramalar; Md Yusop, Hamidah; Hussin, Siti Aishah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Corporate social responsibility is one of the largest and most growing factors that has a potential impact on the organization's performance in the long term. The main purpose of the study was to identify the impact of retailer's corporate social responsibility activities on customer loyalty. The main objective of the study is to determine the relationship between retailers' corporate social responsibility activities and customer loyalty. The quantitative research method was used for this study, and the data was collected randomly from 100 respondents residing in Negeri Sembilan, Malaysia. The several other factors that were examined in this study to gain a better understanding of the impact of corporate social responsibility activities on customer loyalty were corporate reputation, financial benefits, service quality, transparency, and customer loyalty. The results of this study show that people in young and middle ages give the most positive responses. From this study, there is a strong positive relationship between corporate social responsibility and customer loyalty. From this study, it can be seen that people value those companies that constantly engage in social responsibility and meet people's needs and demands by addressing the basic values, beliefs, and morals of society as a whole.